The Effect Of Social Media Platform Use Intensity On Students’ Digital Political Participation - Arlin Nesra Nerista; Ardhana Januar Mahardhani; Sulton (UNIVERSITAS PAKUAN, 2025)
The advancement of information technology has shifted student interactions from traditional communication toward digital engagement, particularly through social media. While social media use among students is relatively high, much of the activity is still dominated by entertainment consumption, raising questions about its impact on digital political participation. This study aims to analyze the effect of social media use intensity on both active and passive forms of digital political participation among students at Universitas Muhammadiyah Ponorogo. A quantitative approach was employed using a survey method involving 305 students. Data were collected through a Likert-scale questionnaire measuring social media use intensity and various forms of digital political participation. Simple linear regression was applied to test the effect of the independent variable on the dependent variable. The findings show that social media use intensity has a positive and significant effect on students’ digital political participation (B = 0.717; p < 0.05; R = 0.289; R² = 0.083). Passive participation dominates, particularly News Attention (76%) and Discussion (65.2%). In terms of active participation, collective actions such as Protest Activities (65.9%) and Consumerism (58.7%) are relatively high, while direct actions such as Contacting (28.5%) and Communal Actions (48.2%) are less frequent. The study highlights the importance of strengthening digital political literacy to ensure that student participation is not only quantitatively high but also qualitatively meaningful. Future research should consider internal factors such as political motivation, digital literacy, and social environment to provide a more comprehensive understanding of the relationship between social media use intensity and digital political participation.